Examining the associations between difficulties in emotion regulation and symptomatic outcome measures among individuals with different mental disorders - Igra, Libby; Shilon, Sharon; Kivity, Yogev; Atzil-Slonim, Dana; Lavi-Rotenberg, Adi; Hasson-Ohayon, Ilanit (Frontiers in Psychology, 2023)
Background: Difficulties in emotion regulation (ER) abilities have been found to play a central role in different psychiatric disorders. However, researchers rarely compare ER across different diagnostic groups. In the current study we examined ER and its relation to functional and symptomatic outcome among three distinct diagnostic groups: people with schizophrenia (SCZ), people with emotional disorders (EDs; i.e., depression and/or anxiety), and individuals without any psychiatric diagnosis (controls). Methods: Participants in this study comprised 108 adults who requested psychotherapy at a community clinic in the year 2015 and between 2017-2019. Clients were interviewed and filled out questionnaires measuring depression, distress, and difficulties in ER abilities. Results: Results showed that individuals with psychiatric diagnoses reported higher levels of difficulties in ER abilities than did controls. Moreover, there were very few differences in levels of ER difficulty between SCZ and EDs. Further, the associations between maladaptive ER and psychological outcomes were significant in each diagnostic group, and especially for SCZ. Conclusions: Our study indicates that difficulties in ER abilities partially have a transdiagnostic nature, and that these difficulties are associated with psychological outcomes among both clinical populations and controls. There were very few differences in levels of ER ability difficulties between SCZ and EDs, suggesting that the two groups share difficulties in relating and responding to emotional distress. The associations between difficulties in ER abilities and outcome were more robust and stronger among SCZ than the other groups, highlighting the potential contribution of targeting ER abilities in the treatment of schizophrenia.